درجة ممارسة معلمي المدارس الثانوية لأخلاقيات مهنة التعليم : المعيقات والحلول - الشياب، محمود; الشرمان، منيرة محمود; الحياري، حسن أحمد الحسن Alhiyari, Hassan Ahmed Alhassan (الجامعة الأردنية - عمادة البحث العلمي, 2018)
هدفت الدراسة الحالية إلى معرفة درجة ممارسة معلمي المدارس الثانوية لأخلاقيات مهنة التعليم في مديرية بني عبيد (المعيقات والحلول)، واستخدم الباحثون المنهج الوصفي المسحي، وتم اختيار عينة عشوائية مكونة من (220) معلما ومديرا، ولغايات تحقيق أهداف الدراسة تم استخدام أداتين للدراسة هما: (الاستبانة والمقابلات)، وأشارت نتائج الدراسة إلى أن درجة ممارسة معلمي المدارس الثانوية لأخلاقيات مهنة التعليم في مديرية بني عبيد جاءت بدرجة مرتفعة، وبناءً على ذلك أوصت الدراسة بضرورة تقليل الاكتظاظ في الصفوف الدراسية، تقليل المهام الإدارية والفنية، كذلك وضع قوانين يلتزم بها الجميع تربويا وتعليميات، بالإضافة إلى وضع قوانين تحفظ هيبة المعلم، بالإضافة إلى التنمية المهنية المستمرة من خلال عقد دورات للمعلمين وخاصة الجدد منهم.
The current study aimed to find out the degree of practicing ethics among secondary schools teachers in Bani Obeid Directorate, the researchers used the descriptive method, the study sample were randomly selected and consisted of (250) teachers and principals. For the purposes of achieving the objectives of the study, the researchers used a questionnaire and interviews. The study results indicated the degree ethics practicing among teachers and managers in secondary schools in Bani Obeid Directorate came highly. In light of the study results the researchers recommended the following: need to reduce overcrowding in classrooms, reduce the administrative and technical tasks, as well as setting rules for everyone to follow educationally and instructions, in addition to the development of laws that protect the prestige of the teacher, and to reduce the burden of teachers, in addition to continuing professional development through holding courses for teachers, especially new teacher.
Keywords: أخلاقيات مهنة التعليم -- المعلم -- مدير المدرسة -- المدارس الثانوية -- مديرية بني عبيد